Assessment of food and nutrition security practices of the artisanal and small-scale mining communities in Nigeria - Adeyinka O. Omotehinse (World Development Sustainability, 2025)
Recently, almost all African countries are experiencing increase in food insecurity thereby failing to meet the 2030 Zero Hunger target. Many artisanal miners in Africa enter the sector because of hardship and spend a significant portion of their income on food purchases. This reliance on limited food sources can lead to malnutrition, which can affect the health and well-being of workers. This study examines the food and nutrition security practices of the artisanal and small-scale mining communities in Nigeria. The methodology include data collection using questionnaires and oral interview. The result highlights interesting insights into various aspects of food accessibility, eating patterns, satisfaction with food vendors, water and health qualities. While there are positive feedbacks, such as miners having access to local food sources, healthy dietary patterns and possessing purchasing power, there are significant challenges related to occasional meal skipping due to insufficient funds, impact of mining on their alternative food source leading to low productivity, water quality, and healthcare access. No provision for healthcare and first aid facilities within mines, price of treatment that pose barriers to affordable healthcare services, and absence of adequate public health insurance schemes. Moreover, having just one healthcare centre can limit the availability and accessibility of medical services. Overall, the findings highlight the need for comprehensive interventions, which include promoting sustainable and nutritious food options, enhancing healthcare infrastructure and affordability, and ensuring access to social protection systems. Such measures can contribute to well-being, productivity, and overall development and sustainable mining practices in Nigeria.